Bias in video evidence: implications for police body cameras - Kalle, Ashley (Applied psychology in criminal justice, 2019)
Camera perspective bias demonstrates that videos of police interrogations focusing on the suspect yield higher ratings of guilt. This bias may generalize to police body camera videos that also focus on the suspect, particularly when observers with strong implicit racial attitudes watch a video with a racial minority suspect. We tested whether focusing on the citizen, police officer, or both influenced perception of a filmed police encounter. Compared to those who watched the officer or both individuals, those who focused on the citizen rated the citizen more negatively and the officer more positively. Participants' implicit racial attitudes significantly predicted judgments of the officer and citizen for all measures.